Distribution of serotypes and virulence genes among invasive, non-invasive and colonizing streptococcus agalactiae (group B streptococcus) isolates from patients in a major teaching hospital in Malaysia - Eskandarian, Narges (2014)
Streptococcus agalactiae also known as group B streptococcus (GBS) remains a significant cause of neonatal sepsis and meningitis worldwide. Approximately 30% of healthy women are colonized with GBS. Main reservoirs are the gastrointestinal and genitourinary tract.GBS pose major threat to the women during their prenatal stage, which are transmitted to fetus during delivery resulting in serious infections and occasional deaths in neonates. It causes early onset diseases (EOD) within 7 days of birth and late onset disease (LOD) from 7 to 90 days. Apart from pregnant women and neonates, GBS infections are also seen in immunocompromised, and elderly patients. Numerous prevention strategies for the control of GBS-related neonatal infections including antibiotic prophylaxis and vaccination have been practiced in many parts of the world. GBS strains vary from country to country; hence, there is a variation in serotype distribution, antibiotic susceptibility and virulence factors of GBS strains, which challenge the management of GBS related infections. In Malaysia, despite of several cases of GBS-related neonates’ infections, data concerning the serotype epidemiology, antibiotic susceptibility and the virulence pattern of local strains are lacking. Therefore, the current study was aimed at determining the serotypes, antibiogram and the virulent gene profile of Malaysian GBS strains. Hundred and three pure cultures of S. agalactiae were obtained from Universiti Kebangsaan Malaysia Medical Center (UKMMC) from June 2010 to October 2011, included 22 invasive, 23 non-invasive and 58 colonizing strains were isolated from clinical samples. Capsular serotyping was performed with the latex agglutination method using specific antisera against types Ia, II-VII CPS antigens. The results of the conventional serotyping (CS) of the strains were further confirmed by molecular serotyping (MS). All conventionally identified serotypes were in agreement with the molecular serotype.Twenty (19.4%) isolates that were non-typable by CS, were also typed by MS. Serotype VI (22.3%), VII (21.3%) were the most common serotypes, and serotype IV (1%) was found to be the least. Antimicrobial susceptibility testing carried out to determine the susceptibility of GBS isolates revealed that all isolates were susceptible to penicillin by both disk diffusion and E-test methods. No resistance was observed for cefuroxime, ceftriaxone, levofloxacin and vancomycin, while resistance rate of 23.3%, 16.5% and 71.8% were seen for erythromycin, clindamycin and tetracycline respectively. Seven virulence genes (cylE, lmb, scpB, hylB, rib, bca, bac) screened on the studied isolates showed the presence of cylE, lmb, scpB and hylB in almost all the isolates while rib, bca, bac genes were found to be present in 29.1%, 14.6% and 9.7% of the isolates.The present study for the first time reports the detection of virulence genes in Malaysian strains. A significant association between rib gene and serotypes Ia, II, III and VI; bca with serotypes II, III and VI; bac with serotypes II and III were observed. In conclusion, this study demonstrated that VI and VII as the predominant serotypes in Malaysia, hence need to be considered while developing vaccines. The antibiotic susceptibility pattern showed local strains are susceptible to penicillin and demonstrated it still could be used as the first choice for GBS treatment. Significant association of virulence factors with certain serotypes need to be routinely monitored to reduce the GBS associated mortality.